Pembatalan Akta Jual Beli Yang Dibuat Oleh Camat Selaku Pejabat Pembuat Akta Tanah Sementara - Cindy Annisa; Suriyaman Suriyaman; Marwah Marwah (ILIN Institute, 2021)
The research objective to analyze the making of the deed of sale and purchase of land carried out by the sub-district head as PPATS with the provisions of the legislation. This study uses empirical research methods. The results of this study, namely: 1) the procedure for making the deed of sale and purchase made by the sub-district head as PPATS is not in accordance with the provisions of the applicable laws because the entire process of making the deed of sale is carried out not before the sub-district head as PPATS but carried out before the lurah and 2) legal protection the buyer of land rights in the case of buying and selling, will get legal protection if he meets the criteria of a buyer with good intentions, namely having made a sale and purchase of the land object in accordance with legal procedures/procedures and documents as determined by law and exercising prudence by examining matters relating to the object of land that is agreed upon based on the Circular Letter of the Supreme Court Number 4 of 2016 concerning the Implementation of the Formulation of the Results of the Plenary Meeting of the Supreme Court Chamber of the Year 2016 as a Guide to the Implementation of Duties for the Court. Penelitian bertujuan untuk menganalisis pembuatan akta jual beli tanah yang dilakukan oleh camat selaku PPATS dengan ketentuan perundang-undangan. Penelitian ini menggunakan metode penelitian empiris. Hasil penelitian ini, yaitu: 1) prosedur pembuatan akta jual beli yang dibuat oleh camat selaku PPATS belum sesuai dengan ketentuan perundang-undangan yang berlaku sebab seluruh proses pembuatan akta jual beli dilakukan tidak dihadapan camat selaku PPATS tetapi dilakukan dihadapan lurah dan 2) Perlindungan hukum terhadap pembeli hak atas tanah dalam hal jual beli, akan mendapatkan perlindungan hukum apabila memenuhi kriteria pembeli beritikad baik yaitu telah melakukan jual beli atas objek tanah sesuai dengan tata cara/prosedur dan dokumen yang sah sebagaimana yang telah ditentukan undang-undang serta melakukan kehati-hatian dengan meneliti hal-hal berkaitan dengan objek tanah yang diperjanjikan berdasarkan Surat Edaran Mahkamah Agung Nomor 4 Tahun 2016 tentang Pemberlakuan Rumusan Hasil Rapat Pleno Kamar Mahkamah Agung Tahun 2016 Sebagai Pedoman Pelaksanaan Tugas Bagi Pengadilan.